2019
DOI: 10.7774/cevr.2019.8.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Absence of neutralizing activity in serum 1 year after successful treatment with antivirals and recovery from MERS in South Korea

Abstract: We evaluated the neutralizing activity in serum from three patients >1 year after recovery from Middle East respiratory syndrome (MERS) associated with mild pneumonia treated with antivirals during the MERS outbreak in South Korea at 2015. The neutralizing activity in serum was measured by pseudovirus inhibition assays. Three-fold diluted serum of subjects showed only 9.7%, 10.3%, and 2.2% reductions in relative light units. So, significant neutralizing activity was not demonstrated in any sera of three patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…Although the rate of seroconversion increased with disease severity, 75% of the deceased MERS-CoV infected patients who developed pneumonia did not seroconvert [45]. Another study by Choi et al demonstrated the absence of neutralizing antibodies one year after successful treatment of MERS-CoV infected patients who had developed mild pneumonia [46]. Their observation is consistent with the previous study where disease severity correlated with seroconversion.…”
Section: Pathogenesis Of Mers-covsupporting
confidence: 81%
See 1 more Smart Citation
“…Although the rate of seroconversion increased with disease severity, 75% of the deceased MERS-CoV infected patients who developed pneumonia did not seroconvert [45]. Another study by Choi et al demonstrated the absence of neutralizing antibodies one year after successful treatment of MERS-CoV infected patients who had developed mild pneumonia [46]. Their observation is consistent with the previous study where disease severity correlated with seroconversion.…”
Section: Pathogenesis Of Mers-covsupporting
confidence: 81%
“…In the same study, MERS survivors with undetectable MERS-CoV-specific antibody responses mounted CD8+ T cell responses [47]. This observation adds more detail to previous studies where neutralizing antibody levels were not detected in MERS survivors and disease severity correlated with seroconversion [45,46]. These observations raise an important question: can MERS-CoV infection be augmented by the presence of antibodies?…”
Section: Role Of T Cells In Mers-cov Infections Has Been Recently Repsupporting
confidence: 76%
“…After calculating the point estimate of the mean for the rest of the studies, which did not report study setting ( Weir et al, 2018 ), the mean age for all COVID-19 cases reached 51.26 ( n = 3122) ( Cai et al, 2020a ; Chen et al, 2020 ; Cheng et al, 2020 ; Du et al, 2020 ; Fan et al, 2020 ; Fernández-Ruiz et al, 2020 Fernández‐Ruiz et al, 2020 ; Huang et al, 2020a ; Huang et al, 2020b ; Hung et al, 2020 ; Jian-ya, 2020 ; Jiang et al, 2020 ; Jin et al, 2020 ; Liao et al, 2020 ; Liu et al, 2020a ; Liu et al, 2020b ; Lo et al, 2020 ; Pan et al, 2020 ; Qiu et al, 2020 ; Rui et al, 2020b ; Sun et al, 2020 ; To et al, 2020 ; Wan et al, 2020 ; Wang et al, 2020a ; Wang et al, 2020b ; Wang et al, 2020c ; Xiao-Wei et al, 2020 ; Yu et al, 2020 ; Yuan et al, 2020 ; Zhou et al, 2020b ). In 24 distinct MERS publications, 1196 patients, including 587 males, 269 females, and 340 whose gender was not reported, were investigated ( Al Ghamdi et al, 2016 ; Al-Hameed et al, 2016 ; Al-Qaseer, 2015 ; Al-Tawfiq and Hinedi, 2018 ; Al-Tawfiq et al, 2014 ; Alfaraj et al, 2019 ; Arabi et al, 2019 ; Cha et al, 2016 ; Choi et al, 2019 ; Choi et al, 2016 ; Garout et al, 2018 ; Habib et al, 2019 ; Khalid et al, 2016 ; Khalid et al, 2015 ; Khalid et al, 2014 ; Kim et al, 2017 ; Kim et al, 2016 ; Lee et al, 2017 ; Malik et al, 2016 ; Oh et al, 2015 ; Omrani et al, 2014 ; …”
Section: Resultsmentioning
confidence: 99%
“…In 24 distinct MERS publications, 1196 patients, including 587 males, 269 females, and 340 whose gender was not reported, were investigated ( Al Ghamdi et al, 2016 ; Al-Hameed et al, 2016 ; Al-Qaseer, 2015 ; Al-Tawfiq and Hinedi, 2018 ; Al-Tawfiq et al, 2014 ; Alfaraj et al, 2019 ; Arabi et al, 2019 ; Cha et al, 2016 ; Choi et al, 2019 ; Choi et al, 2016 ; Garout et al, 2018 ; Habib et al, 2019 ; Khalid et al, 2016 ; Khalid et al, 2015 ; Khalid et al, 2014 ; Kim et al, 2017 ; Kim et al, 2016 ; Lee et al, 2017 ; Malik et al, 2016 ; Oh et al, 2015 ; Omrani et al, 2014 ; Rhee et al, 2016 ; Shalhoub et al, 2015 ; Sherbini et al, 2017 ). The mean age for patients with MERS was 53.58 ( n = 464) for 17 studies ( Al-Qaseer, 2015 ; Al-Tawfiq and Hinedi, 2018 ; Al-Tawfiq et al, 2014 ; Alfaraj et al, 2019 ; Cha et al, 2016 ; Choi et al, 2019 ; Habib et al, 2019 ; Khalid et al, 2015 ; Khalid et al, 2014 ; Kim et al, 2017 ; Kim et al, 2016 ; Lee et al, 2017 ; Malik et al, 2016 ; Oh et al, 2015 ; Omrani et al, 2014 ; Rhee et al, 2016 ; Sherbini et al, 2017 ), and after estimation of missing mean age reached 53.33 ( n = 1170) for all eligible MERS studies ( Al Ghamdi et al, 2016 ; Al-Hameed et al, 2016 ; Al-Qaseer, 2015 ; Al-Tawfiq and Hinedi, 2018 ; Al-Tawfiq et al, 2014 ; Alfaraj et al, 2019 ; Arabi et al, 2019 ; Cha et al, 2016 ; Choi et al, 2019 ; Choi et al, 2016 …”
Section: Resultsmentioning
confidence: 99%
“… 12 13 Immunity to colds is less than half a year, and immunity to severe acute respiratory syndrome or Middle East respiratory syndrome coronavirus is about 1-3 years, which is based on the results of small-scale. 14 15 16 In any case, it is certain that immunity against coronavirus is not permanent, so even if herd immunity is formed, there is no way to stop getting it again when the seasons change.…”
Section: Sweden's Lenient Strategy Against Covid-19mentioning
confidence: 99%